Perhitungan, Pemotongan, dan Pelaporan PPh Pasal 23 terhadap Layanan Outsourcing pada PT GHI - Azahra, Raudhatul; Widodo, Condro (IAI Nasional Laa Roiba Bogor, 2024)
Tax is a mandatory contribution collected by the government from the community without compensation received directly by the taxpayer. This means that when someone pays taxes, they do not receive a specific direct benefit from that payment. On the other hand, taxes are used for public interests and public services whose benefits are felt by society as a whole. The tax imposed on income in accordance with Article 23 is one of the crucial elements in the Indonesian tax system which makes a significant contribution to state revenue. One of the objectives of PPh Article 23 is to provide outsourcing services. For this reason, the purpose of this research is to understand how income from outsourcing services at PT GHI is calculated, deducted and reported on income tax based on Article 23. The approach applied in this research is qualitative descriptive using interviews and documentation. The results of this study support the conclusion that the calculation, withholding and reporting of PPh 23 at PT GHI has complied with all relevant legal requirements, namely at an amount of 2% and those who carry out the withholding and reporting of PPh 23 are the parties receiving the services.